The Effect of Principal's Academic Supervision and Work Commitment on Teachers' Teaching Performance at SMK N 1 Barumun, Padang Lawas District, North Sumatera Province - Gultom, Sarah Nadiyah; Azhar, Fadly; Erlisnawati, Erlisnawati (Journal Corner of Education, Linguistics, and Literature, 2024)
This study aims to determine the Influence of Principal's Academic Supervision and Work Commitment on Teachers' Teaching Performance at SMK N 1 Barumun, Padang Lawas Regency. This type of research is quantitative with the method used in this study is a survey method with a sampling technique, namely Random sampling, namely random sampling. The data collection technique used in this study is a questionnaire using a Likert scale. The results of this study indicate that there is an Influence of Principal Academic Supervision and Work Commitment on Teacher Teaching Performance with an F count of 68.091 and a significance of 0.000. Using the level of ???? (Alpha) = 0.05 or 5% shows that the calculation of f count 68.091> ftable 3.11 and the Sig. value. (0.000) <0.05, it can be concluded that the variables of academic supervision (X1) and work commitment (X2) simultaneously have a significant influence on teacher teaching performance at SMKN 1 Barumun, Padang Lawas Regency. and its significance is less than 0.05 (0.000 <0.05) meaning that ????a is accepted and ????0 is rejected. This means that partially there is a significant influence of Principal Academic Supervision and Work Commitment on Teacher Teaching Performance at SMK N 1 Barumun, Padang Lawas Regency. R2 value of 0.636, this means that the variables of academic supervision and work commitment contribute to the teacher performance variable by 63.6%, while the remaining 36.4% is influenced by other variables not examined in this study. This shows a significant influence of the Principal's Academic Supervision and Work Commitment on Teacher Teaching Performance at SMK N 1 Barumun, Padang Lawas Regency.